Measuring and modeling the shrinkage characteristics of plastic clays - Nurulain , Mohamed Hatta (2012)
Clayey soils are generally used as liner material in landfill to prevent ground water pollution. The swelling and shrinkage soils are affected the change in the water content. Significant shrinkage caused by loss of pore water in clays may cause enormous damage to liner systems. This study presents the shrinkage behaviour of KB soil and MX80 bentonite from saturated condition under zero applied stress. Duplicate specimens were prepared at different water contents and the volumes of the soils were experimentally measured using wax method. The shrinkage characteristic curves (SSCC) were then established. In addition, continuous SSCC were also established using Kea model and compared with the experimental SSCC. The SSCC enabled the determination of shrinkage limits and the air entry value (AEV). Furthermore, the void ratios at consistency limits were identified. The void ratios obtained for KB soil in term of liquid limit (eLjj, plastic limit (epL), shrinkage limit (esL); and at air entry (eAEV) are 1.16, 0.88, 0.59 and 0.94 respectively. Meanwhile, the void ratios (e) obtained for MX80 bentonite in term of liquid limit (eLL), plastic limit (epL), shrinkage limit (esL); and at air entry (eAEV) are 12.24, 1.76, 0.34 and 0.40, respectively. Kea model can be used to establish a continuous shrinkage path of soil having two shrinkage phases with some limitations. Furthermore, it was noted that, the fitting parameters (i.e. the slope parameter depending on the air entry value (8) and slope of the saturation line found to be different for different soil of different physical properties and different mineral compositions.((P)) were